Statins and Peripheral Arterial Disease: A Narrative Review - Jansen-Chaparro, Sergio; López-Carmona, María D.; Cobos-Palacios, Lidia; Sanz-Cánovas, Jaime; Bernal-López, M. Rosa; Gómez-Huelgas, Ricardo (Frontiers in Cardiovascular Medicine, 2021)
Peripheral arterial disease (PAD) is a highly prevalent atherosclerotic condition. In patients with PAD, the presence of intermittent claudication leads to a deterioration in quality of life. In addition, even in asymptomatic cases, patients with PAD are at high risk of cardiac or cerebrovascular events. Treatment of PAD is based on lifestyle modifications; regular exercise; smoking cessation; and control of cardiovascular risk factors, including hypercholesterolemia. A growing number of studies have shown that statins reduce cardiovascular risk and improve symptoms associated with PAD. Current guidelines recommend the use of statins in all patients with PAD in order to decrease cardiovascular events and mortality. However, the prescribing of statins in patients with PAD is lower than in those with coronary heart disease. This review provides relevant information from the literature that supports the use of statins in patients with PAD and shows their potential benefit in decreasing lower limb complications as well as cardiovascular morbidity and mortality.